2002
DOI: 10.1046/j.0962-1083.2001.01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Social structure in migrating humpback whales (Megaptera novaeangliae)

Abstract: Although largely solitary, humpback whales exhibit a number of behaviours where individuals co-operate with one another, for example during bubble net feeding. Such cases could be due to reciprocal altruism brought on by exceptional circumstances, for example the presence of abundant shoaling fish. An alternative explanation is that these behaviours have evolved through kin selection. With little restriction to either communication or movement, diffuse groups of relatives could maintain some form of social org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 40 publications
5
61
0
Order By: Relevance
“…the wall of bubbles, and so are trapped within the 'bubble net', making an easy meal for the whales when they swim up from the base of the net, mouths agape (Sharpe, Dill, 1997;Valsecchi et al, 2002). The reason why fish and other prey do not cross the bubble wall was not clear.…”
Section: Do Whales Call In Spirals?mentioning
confidence: 99%
“…the wall of bubbles, and so are trapped within the 'bubble net', making an easy meal for the whales when they swim up from the base of the net, mouths agape (Sharpe, Dill, 1997;Valsecchi et al, 2002). The reason why fish and other prey do not cross the bubble wall was not clear.…”
Section: Do Whales Call In Spirals?mentioning
confidence: 99%
“…These individuals include a sub-sample of the whales previously analysed at the nDNA level by Valsecchi et al 2002. Here we integrated also singletons or whales which were the only sampled member in pods of 2 or more individuals: these individuals, for the purpose of the research, were excluded in the previous study (Valsecchi et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…In some populations, males comprise the majority of migrating animals , Craig & Herman 1997, indicating that females do not migrate every year. Analyses of nuclear DNA variation in migrating ani-mals indicate that whales do not migrate in kin-based social units (Valsecchi et al 2002, Pomilla & Rosenbaum 2006.…”
Section: Introductionmentioning
confidence: 99%
“…However, the non significant F IS -value and the high genetic variability existing within social groups indicated that the population did not suffer from inbreeding. This might be explained by the fact that sperm whales have evolved complex social behaviours, including behavioural mechanisms that minimize inbreeding amongst individuals (Valsecchi et al 2002;Whitehead 2003). One of these mechanisms is the selective dispersal of males associated to female philopatry (Pusey and Wolf 1996).…”
Section: Polymorphismmentioning
confidence: 99%